ENACTING AGENCY IN INFORMAL LEARNING: AN ECOLOGICAL STUDY OF EFL LEARNERS’ PODCAST USE FOR VOCABULARY DEVELOPMENT - Melisa Sri; Emi Emilia; Raden Safrina (Indonesian EFL Journal, 2025)
Podcasts have emerged as an accessible, flexible, and learner-centered resource in informal English vocabulary development. While learner autonomy and digital vocabulary learning have been studied, limited research has investigated how EFL learners exercise agency when using podcasts in informal settings, particularly through a theoretically grounded lens. This study explores how EFL learners enact agency in vocabulary learning through podcasts, using Priestley et al.’s (2015) ecological model of agency, which incorporates iterational, practical-evaluative, and projective dimensions. Adopting a qualitative phenomenological design, the study involved eight EFL learners who regularly used podcasts for vocabulary learning. Data were gathered through semi-structured interviews and reflective journals and analyzed thematically. The findings show that learners’ agentic engagement is shaped by past learning experiences, present decision-making strategies, and future language goals. Participants demonstrated autonomy in selecting content, integrating podcasts into their routines, and using supplementary digital tools. Their engagement was guided by previous experiences with formal learning, personal beliefs about language acquisition, and aspirations for academic or professional success. The study concludes that learner agency is a dynamic, contextually situated, and future-oriented process, and that podcasts offer a meaningful platform for enacting such agency in vocabulary development beyond the classroom.